Effect of different substrates on growth and yield of Oyster mushroom (Pleurotus sajor-caju) in Eastern parts of Bihar - Chand, Gireesh; Kumar, Santosh; Kumar, Amarendra; Kumari, Baby (Mushroom Research, 2016)
Oyster Mushroom (Pleurotus sajor-caju), commonly known as Dhingri is an important edible mushrooms gaining popularity in recent years because of its high nutritional value and ability to grow on diverse agricultural wastes. The genus is characterized by its high protein content 30- 40% on dry weight basis which is twice that of vegetable. Different grain based spawn also influenced the duration of spawn run and pin head formation as well as the biological efficiency of mushroom. The present investigation aims to study the different substrates namely paddy straw, wheat straw, maize stalk, lentil straw, banana pseudostem and Water Hyacinth for growth (Biological Efficiency) and yield of oyster mushroom. Among all the substrates, paddy straw resulted in higher yield (296.0g/500g) and biological efficiency (60.0%) followed by wheat straw i.e., 209.5g/500g and 42.0% and lowest fruit yield (17g/500g) was recorded with water hyacinth while, biological efficiency with lentil straw (13.1%). The study revealed that faster mycelial growth is consistent with better yield and highest biological efficiency.Â